Interactive Learning Model to Improve Student Activities and Learning Outcomes of SMP Negeri 29 Makassar - Nova Dwi Pratiwi Sulastri; Muh Yahya; Jetti; Endang Kartini Supeni; Astri; Sri Megawati; Wahyuni Limonu (MultiTech Publisher, 2024)
The educational process in higher education institutions no longer only prioritizes the acquisition of information, but rather focuses more on the development of skills and information processing. Therefore, it is necessary to increase student activity through group exercises or assignments and expression of ideas to peers. This has attracted the attention of researchers to observe how students learn in class when given an interactive learning model that is different from conventional methods. Based on the results of observations in class IX.6 SMP 29 Makassar, a problem was found where the monotonous learning process by the teacher and the initial pretest showed several students with low (D) and failed (E) scores. It can be concluded that the low learning outcomes are also influenced by the lack of student learning activities. This type of research is Classroom Action Research (CAR) with subjects of class IX.6 SMP 29 Makassar students. The research was conducted for two cycles with four meetings. The results of the study indicate that the application of an interactive learning model can improve student learning activities in the Introduction to Education course in Biology B class, Patompo University. The average percentage of student learning activities in cycle I was 56.55%, increasing to 81.55% in cycle II. Therefore, there was an increase of 25.00% from cycle I to cycle II. In addition, the use of interactive learning models also had a positive impact on student learning outcomes. The average post-test score of students in cycle I was 70, increasing to 81.43 in cycle II. Thus, there was an increase in the average value of learning outcomes of 11.43% from cycle I to cycle II.